Polymorphism of human telomeric quadruplex structure controlled by DNA concentration: a Raman study - Palacký, Jan; Vorlíčková, Michaela; Kejnovská, Iva; Mojzeš, Peter (Nucleic acids research, 2013)
DNA concentration has been recently suggested to be the reason why different arrangements are revealed for K(+)-stabilized human telomere quadruplexes by experimental methods requiring DNA concentrations differing by orders of magnitude. As Raman spectroscopy can be applied to DNA samples ranging from those accessible by absorption and CD spectroscopies up to extremely concentrated solutions, gels and even crystals; it has been used here to clarify polymorphism of a core human telomeric sequence G(3)(TTAG(3))(3) in the presence of K(+) and Na(+) ions throughout wide range of DNA concentrations. We demonstrate that the K(+)-structure of G(3)(TTAG(3))(3) at low DNA concentration is close to the antiparallel fold of Na(+)-stabilized quadruplex. On the increase of G(3)(TTAG(3))(3) concentration, a gradual transition from antiparallel to intramolecular parallel arrangement was observed, but only for thermodynamically equilibrated K(+)-stabilized samples. The transition is synergically supported by increased K(+) concentration. However, even for extremely high G(3)(TTAG(3))(3) and K(+) concentrations, an intramolecular antiparallel quadruplex is spontaneously formed from desalted non-quadruplex single-strand after addition of K(+) ions. Thermal destabilization or long dwell time are necessary to induce interquadruplex transition. On the contrary, Na(+)-stabilized G(3)(TTAG(3))(3) retains its antiparallel folding regardless of the extremely high DNA and/or Na(+) concentrations, thermal destabilization or annealing.
Keywords: Telomere; telomery; Ramanova spektroskopie; Potassium; Spectrum Analysis, Raman; G-kvadruplexy; G-Quadruplexes; Humans; Temperature; teplota; DNA; draslík; lidé